Tragedy and Theory : the Problem of Conflict Since Aristotle. - Zerba, Michelle, 1953- (Princeton legacy library., 2014)
Michelle Gellrich engages current debates about the relationship between literature and theory by analyzing responses of theorists in the Western tradition to tragic conflict. Isolating the centrality of conflict in twentieth-century definitions of tragedy, Professor Gellrich discusses the efforts of modern critics to locate in Aristotle's Poetics the origins of this focus on agon. Through a study of ethical and political ideas formative of the Poetics, she demonstrates why Aristotle and his Renaissance and Neoclassical beneficiaries exclude conflict from their accounts of tragedy. The agon.